Peningkatan Komitmen Organisasi melalui Penguatan Efikasi Diri dan Kualitas Kehidupan Kerja - Qurbani, Derita; Solihin, Dede (Jurnal Bisnis dan Manajemen, 2021)
Competition for universities in Indonesia, especially private universities, is always getting tougher every year. The number of existing private universities increasingly provides competitive value with the aim of working on prospective students so that the chosen institution or college remains superior and attractive and remains in demand. The purpose of this study was to examine the effect of self-efficacy and quality of work life on organizational commitment. This type of research is quantitative research using the causality method. The sample in this study was 135 respondents obtained from purposive sampling technique. Data was collected using a questionnaire, while data analysis was carried out using Partial Least Squares (PLS). The results showed that self-efficacy and the quality of work life had an effect on organizational commitment.